EffECTively Treating Depression: A Pilot Study Examining Manualized Group CBT as Follow-Up Treatment After ECT - Carstens, Luisa; Hartling, Corinna; Aust, Sabine; Domke, Ann-Kathrin; Stippl, Anna; Spies, Jan; Brakemeier, Eva-Lotta; Bajbouj, Malek; Grimm, Simone (Frontiers in Psychology, 2021)
Background: There is an urgent need for effective follow-up treatments after acute ECT in depressed patients. Preliminary evidence suggests psychotherapeutic interventions to be a feasible and efficacious follow-up treatment. However, there is a need for research on the long-term usefulness of such psychotherapeutic offers in a naturalistic setting that is more representative of routine clinical practice. Therefore, the aim of the current pilot study was to investigate the effects of a half-open continuous group CBT with CBASP elements as a follow-up treatment for all ECT patients, regardless of response status after ECT, on reducing depressive symptoms and promoting psychosocial functioning. Method: Group CBT was designed to support patients during the often-difficult transition from inpatient to outpatient treatment. In a non-controlled pilot trial, patients were offered 15 weekly sessions of manualized group CBT (called EffECTiv 2.0). The Montgomery-Åsberg Depression Rating Scale (MADRS) was assessed as primary outcome, the Beck Depression Inventory (BDI-II), WHO Quality of Life Questionnaire – BREF (WHOQOL-BREF) and the Cognitive Emotion Regulation Questionnaire (CERQ) were assessed as secondary outcomes. Measurements took place before individual group start, after individual group end and six months after individual group end. Results: During group CBT, Post-ECT symptom reduction was not only maintained but there was a tendency towards a further decrease in depression severity. This reduction could be sustained six months after end of the group, regardless of response status after ECT treatment. Aspects of quality of life and emotion regulation strategies improved during group CBT and these improvements were maintained six months after the end of the group. Conclusion: Even though the interpretability of the results is limited by the small sample and the non-controlled design, they indicate that manualized group CBT with CBASP elements might pose a recommendable follow-up treatment option after acute ECT for depressed patients, regardless of response status after ECT. This approach might not only help to further reduce depressive symptoms and prevent relapse, but might also promote long-term psychosocial functioning by improving emotion regulation strategies and psychological quality of life and thus could be considered as a valuable addition to clinical routine after future validation.